Board Member Age Diversity and Financial Performance of Manufacturing Firms: A Developing Economy Perspective - Akisimire, Richard; Salim, Muhsin; Mutahyoba, Masoud; Baisi, D.; Orobia, Laura A. (Journal of Economics and Behavioral Studies, 2016)
This paper examines the relationship between board member age diversity and financial performance of manufacturing firms in Uganda. A cross section survey research design was employed using 78 manufacturing firms across the country. Data was analysed using descriptive statistics, chi-square analysis and point bi-serial correlation. The results showed that majority of the boards had members with an average age of 35-44years, followed by 25-34 years. In addition, boards comprising of majorly young board members registered low performance level, compared to the boards comprising of majorly older members. Further, the results indicated that board member age diversity is significantly associated with financial performance of manufacturing firms. Like any other research study, this study is limited in the following ways. Since only a single research methodological approach was employed, future research could undertake a mixed approach and triangulate to validate the current findings. Further, a longitudinal approach should be employed to study financial performance trends among manufacturing firms over years. Finally, board member age diversity was studied and by virtual of the results, there are other factors that explain the financial performance of the Uganda’s manufacturing sector that were not part of this study
Keywords: Age diversity; financial performance; manufacturing firms; board member